Regras de política monetária para o Brasil: Uma análise para as regras de Taylor, McCallum e suas variantes híbridas - Souza, Abner Silvestre de (2025)
As monetary policy rules play a fundamental role in the functioning of the Inflation Targeting Regime, serving as instruments to guide monetary policy implementation and align market expectations. The adoption of clear rules, such as the Taylor Rule and its variants, contributes to the predictability of Central Bank actions, strengthening its credibility and facilitating inflation control. These rules provide a structured framework for decision-making, allowing the Central Bank to respond to inflationary deviations and external pressures while minimizing economic volatility. Thus, the objective of this study was to analyze the adequacy of the McCallum Rule, the McCallum-Hall-Mankiw Hybrid Rule, and the McCallum-Taylor Hybrid Rule to the Brazilian economic scenario, focusing on their comparison with the Taylor Rule. To this end, estimation was carried out using Vector Error Correction Models (VECM) for the period from March 2002 to January 2024. The main findings indicate that the McCallum-Taylor Rule is more reactive to economic fluctuations, whereas the McCallum-Hall-Mankiw Rule is broader, responding to a wider set of factors, including inflation expectations. Additionally, while the McCallum-Taylor Hybrid Rule is less responsive to exchange rate variations, the McCallum-Hall-Mankiw Rule can incorporate these variations indirectly through their influence on inflation expectations and economic activity. Keywords: Monetary Policy; Interest Rates; VECM; Inflation. JEL Classification Code: E52, E58, E43